The effect of dexmedetomidine on hemodynamic parameters during neuro-oncological surgery - M. V. Rumiantceva; L. M. Tsentsiper; A. N. Kondratyev (Вестник анестезиологии и реаниматологии)
Introduction. The use of alpha 2-adrenoagonist dexmedetomidine, as an adjuvant for anesthesiological aid in neuro-oncological surgery, allows to create and maintain stable hemodynamics throughout the entire surgical intervention. The observed hemodynamic effects depend on the dose of dexmedetomidine.The objective was to evaluate the effect of the highly selective alpha2-adrenoagonist dexmedetomidine on hemodynamic parameters during anesthesia in surgeries for the removal of a brain tumor.Materials and methods. The study included 92 patients operated on for a brain tumor. The division into groups was carried out depending on the dosage of dexmedetomidine and the position on the operating table. In group 1 (n = 58), dexmedetomidine was used, which was administered during the first 30–40 minutes at a rate of 1.4 ± 0.4 mkg/kg/h, and after introductory anesthesia at a maintenance dosage of 0.4 ± 0.2 mkg/kg/h. In group 2 (n = 34), dexmedetomidine was administered during the first 30–40 minutes at a rate of 0.7 ± 0.1 mkg/kg/h, and after induction of anesthesia with a maintenance dosage of 0.2 ± 0.1 mkg/kg/h. Subgroup A – patients operated in a sitting position, subgroup B – patients operated in a lying position.Results. More stable hemodynamics and mild parasympathicotonia were noted at all stages of surgery when dexmedetomidine was used at an initial dose of 0.7 ± 0.1 mkg/kg/h and a maintenance dose of 0.2 ± 0.1 mkg/kg/h. Conclusion. The study revealed that the optimal dosage of dexmedtomidine to achieve a central sympathomodulating effect is 0.7 ± 0.1 mkg/kg/h in the initial stages and 0.2 ± 0.1 mkg/kg/h in the maintenance.